Penilaian Kualitas Berbasis Model FURPS pada Aplikasi Web SIMPONI Universitas XYZ - Patricia, Grace; Yulistia, Yulistia (STMIK Banjarbaru, 2026)
This study evaluates the quality of the SIMPONI web application at XYZ University, which experienced technical problems after two years of operation. The objective of the study was to analyze the system quality using the FURPS (Functionality, Usability, Reliability, Performance, Supportability) model. The method used was a mixed method involving 327 students through questionnaires and interviews with the Information Systems UPT team. The results showed that the Performance dimension had the lowest score (mean 2.55) due to the surge in users, followed by Reliability (mean 2.73) related to system stability. Meanwhile, the other dimensions were in the fairly good category (mean > 3.4). The instrument was declared valid and reliable with a Cronbach's Alpha of 0.96. This study concluded the need for server infrastructure improvements and periodic system optimization to improve the user experience.Kata kunci: FURPS; Software Quality; Academic Information Systems; SIMPONI; Web-Based ApplicationsAbstrakPenelitian ini mengevaluasi kualitas aplikasi web SIMPONI di Universitas XYZ yang mengalami kendala teknis setelah dua tahun beroperasi. Tujuan penelitian adalah menganalisis kualitas sistem menggunakan model FURPS (Functionality, Usability, Reliability, Performance, Supportability). Metode yang digunakan adalah mixed method dengan melibatkan 327 mahasiswa melalui kuesioner dan wawancara bersama tim UPT Sistem Informasi. Hasil penelitian menunjukkan bahwa dimensi Performance memiliki skor terendah (mean 2,55) akibat lonjakan pengguna, disusul oleh Reliability (mean 2,73) terkait stabilitas sistem. Sementara itu, dimensi lainnya berada pada kategori cukup baik (mean > 3,4). Instrumen dinyatakan valid dan reliabel dengan Cronbach's Alpha 0,96. Penelitian ini menyimpulkan perlunya peningkatan infrastruktur server dan optimasi sistem secara berkala untuk meningkatkan pengalaman pengguna.